Horizontal force production and multi-segment foot kinematics during the acceleration phase of bend sprinting - Judson, L. J.; Churchill, S. M.; Barnes, A.; Stone, J. A.; Brookes, I. G. A.; Wheat, J. (Scandinavian Journal of Medicine & Science in Sports, 2019)
This paper investigated horizontal force production, foot kinematics and metatarsophalangeal (MTP) joint push-off axis use during acceleration in bend (anti-clockwise) and straight-line sprinting. It was hypothesised that bend sprinting would cause the left step push-off to occur about the oblique axis, resulting in a decrease in propulsive force. Three-dimensional kinematic and ground reaction force data were collected from nine participants during sprinting on the bend (36.5 m radius) and straight. Anteroposterior force was reduced at 38-44% of stance during bend sprinting compared with the straight. This coincided with an increase in mediolateral force for the majority of the stance phase (3-96%) on the bend compared with the straight. In addition, a lower propulsive impulse was reported on the bend compared with the straight. Analysis of multi-segment foot kinematics provides insight into the possible mechanisms behind these changes in force production. Mean mediolateral centre of pressure position was more lateral in relation to the second metatarsal head in the left step on the bend compared with the straight, indicating the oblique axis was used for push-off at the MTP joint. Greater peak joint angles of the left foot were also reported, in particular, an increase in left step midfoot eversion and internal ankle rotation. It is possible these changes in joint kinematics are associated with the observed decrease in propulsive force. Therefore, practitioners should seek to strengthen muscles such as tibialis posterior in frontal and sagittal planes and ensure specificity of training which may aid in addressing these force reductions.